Large intra-thoracic desmoid tumor with airway compression: A case report and review of the literature - Tyler D. Robinson; Matias Bruzoni; Peter Than; Safwan Halabi; James Wall (Journal of Pediatric Surgery Case Reports, 2016)
Intra-thoracic desmoid tumors are exceedingly rare tumors in the pediatric population, and can present with compression of cardiopulmonary structures and respiratory compromise. Surgical and anesthetic management of these tumors are challenging. We report the case of a 14-year-old male who presented with dyspnea, found to have a large intra-thoracic mass that was critically compressing his trachea. We provide a review of the literature of desmoid tumors and discuss the management of intra-thoracic masses.